Magnetic particle imaging signal acquisition using second harmonic detection of magnetic nanoparticles - Muhammad Mahadi Abdul Jamil; Abdulkadir Abubakar Sadiq; Muhammad Shukri Ahmad; Noordin Asimi Mohd Noor; Nur Adilah Abd Rahman; Nurmiza Othman (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents an approach for acquiring a magnetic particle imaging (MPI) signal, by utilizing the second harmonic detection of the magnetic nanoparticles tracers. An MPI signal with high signal-to-noise ratio (SNR) is crucial for high spatial resolution images that reveals the distribution of the tracers in a target area. Samples of Resovist and Perimag nanoparticles tracers were prepared in liquid and immobilised form, which were placed at some distances under the receiver coil of the single-sided MPI scanner. The samples were exposed to the excitation magnetic field generated at 22.8 kHz and a static gradient field generated with a direct current of 2 A. The non-linear magnetization response of the tracers for each spatial position is recorded in the form of voltage signal by a gradiometer pickup coil, with the second harmonic signal being extracted by a resonance circuit. The results obtained revealed that a sufficient signal from the tracers is recorded at up to 25 mm under the pickup coil, with Perimag samples inducing higher signals as compared to Resovist. The dependence of the DC gradient field on the second harmonic signal shows that the peak signal amplitude for Resovist and Perimag particles as ±5 mT and ±6 mT respectively. Additionally, the second harmonic signal amplitude increases exponentially with an increase in the excitation magnetic field. Thus, the results obtained shows the potential of this approach in acquiring high SNR MPI signals at low excitation frequency, which could be vital in reconstructing the contour images of the tracers, particularly in sentinel lymph node biopsy (SLNB) for breast cancer diagnosis.